THE ANALYSIS OF SPEECH FUNCTION USED BY ENGLISH TEACHERS AT SMAN 5 KENDARI - Yuliana, Yuliana; Suhartini, Lelly; Rohmana, Rohmana (Universitas Halu Oleo, 2019)
Speech function that used in delivering instructional process is important because a major part of class time in learning process is taken up by teachers. Teachers should use speech function appropriate with the classroom context. This study applied speech function theory to analyse functional speech of teacher‟s utterances. This study investigated the speech function used by English teachers in language instruction. The objectives of this study were to find out the types of speech function and the accuracy of speech functions used by English teachers at SMAN 5 Kendari. This study employed a qualitative research design. The techniques of data collection were documentation and observation. To analyse the data, the researcher used descriptive analysis. The result of this study showed that there are five types of speech function and they are accurately used by English teachers in giving instruction.Keywords: Speech Function, Accuracy, Context